Report-dependent utility and strategy-proofness - Vincent Meisner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
Despite the truthful dominant strategy, participants in strategy-proof me- chanisms submit manipulated preferences. In our model, participants dislike rejections and enjoy the confirmation from getting what they declared most desirable. Formally, the payoff from a match decreases in its position in the submitted ranking such that a strategic trade-off between preference intensity and match probability arises. This trade-off can trigger the commonly observed self-selection strategies. We show that misrepresentations can persist for arbitrarily small report-dependent components. However, honesty is guaranteed to be optimal if and only if there is no conflict between the quality and feasibility of a match.
Keywords: D47; D78; D81; D91; 330; Market design; matching; school choice; self-regarding preferences; strategy-proof mechanisms